2004
DOI: 10.1002/crat.200310161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of density of states on optical properties of GaSe thin film

Abstract: A systematic investigation on the effect of substrate temperature on the structure, optical absorption and density of states of vacuum evaporated gallium monoselenide (GaSe) thin films is reported. The X-ray diffraction analysis shows an occurrence of amorphous to polycrystalline transformation in the films deposited at higher-temperature substrates (573K). The compositional analysis is made with Auger Electron Spectroscopy (AES). The thickness of the film (175nm) is measured by a multiple beam interferometery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The dependence of (αhω) 1/P on the photon energy (hω) was examined for different values of P and the results showed (αhω) 1/2 varies linearly with (hω), indicating a non-direct optical transition with energy 1.8 eV, in good agreement with the reported value for the sputtered GaSe films [14] and in contradictory with the reported results for thermally evaporated GaSe film [16]. Fig.…”
Section: Refractive Index Dispersion Analysissupporting
confidence: 55%
See 1 more Smart Citation
“…The dependence of (αhω) 1/P on the photon energy (hω) was examined for different values of P and the results showed (αhω) 1/2 varies linearly with (hω), indicating a non-direct optical transition with energy 1.8 eV, in good agreement with the reported value for the sputtered GaSe films [14] and in contradictory with the reported results for thermally evaporated GaSe film [16]. Fig.…”
Section: Refractive Index Dispersion Analysissupporting
confidence: 55%
“…The presence of indirect optical transition was also supported with dissimilar energies values of 1.83 and 1.5 eV for sputtered [14] and vacuum evaporated amorphous GaSe film [15], respectively. Furthermore, other work revealed two indirect and one forbidden direct optical transitions with energies 1.1, 1.44 and 1.92 eV, for thermally evaporated GaSe films [16].…”
Section: Introductionmentioning
confidence: 98%
“…The presence of non-direct optical transition was also supported with dissimilar energy values of 1.83 and 1.5 eV for sputtered [14] and vacuum evaporated amorphous GaSe film [15], respectively. Furthermore, other work revealed two non-direct and one forbidden direct optical transitions with energies 1.1, 1.44 and 1.92 eV, for thermally evaporated GaSe films [16]. Such contradictory results in the earlier studies, in addition to the fact that there is only one published work that considered the wavelength dependence of refractive index in the visible range for amorphous GaSe films [13], motivated us to undertake the present study.…”
mentioning
confidence: 90%
“…The dependence of photo-current on the illumination intensity revealed the existence of two recombination centers in the GaSe crystals. Thamilselvan et al [12] reported the influence of heating the substrate on the conduction mechanism of the polycrystalline and amorphous GaSe thin films. Very recently, Siciliano et al [13] have investigated the influence of thermal oxidation on the GaSe thin film.…”
Section: Introductionmentioning
confidence: 99%